2023
DOI: 10.1002/adem.202300182
|View full text |Cite
|
Sign up to set email alerts
|

The Modeling of Magnetorheological Elastomers: A State‐of‐the‐Art Review

Abstract: The magnetorheological elastomers (MREs) are novel multifunctional materials wherein their viscoelastic properties can be varied instantly under an application of applied magnetic field. Due to their field‐dependent stiffness and damping properties, MREs are widely used in the development and design of MRE‐based adaptive vibration isolators and absorbers and also biomedical engineering. Moreover, MREs due to their inherent magnetostriction effect have enormous potential for the development of soft actuators. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 343 publications
0
4
0
Order By: Relevance
“…One such model was derived in Bustamante [44] and involves 10 invariants (nine for incompressibility) in the general case. It was used in the review paper by Saber & Sedhagati [45] in the study of constitutive models of the nonlinear behaviour of MS elastomers, including micro-structural models. where e = tre and the constants μ, λ, ν and ξ are given by the derivatives Ω i and Ω ij being evaluated in B 0 .…”
Section: Materials Symmetrymentioning
confidence: 99%
See 1 more Smart Citation
“…One such model was derived in Bustamante [44] and involves 10 invariants (nine for incompressibility) in the general case. It was used in the review paper by Saber & Sedhagati [45] in the study of constitutive models of the nonlinear behaviour of MS elastomers, including micro-structural models. where e = tre and the constants μ, λ, ν and ξ are given by the derivatives Ω i and Ω ij being evaluated in B 0 .…”
Section: Materials Symmetrymentioning
confidence: 99%
“…Several slightly different approaches have been developed in the literature, including those by Brigadnov & Dorfmann [41], Kankanala & Triantafyllidis [42], Dorfmann & Ogden [26], and a novel theory based on implicit constitutive equations has been developed by Bustamante & Rajagopal [43]. A constitutive theory for transversely isotropic magnetoelastic materials was proposed by Bustamante [44], and has been used in the review by Saber & Sedaghati [45]. The method of homogenization has been used by Castañeda & Galipeau [46], Chatzigeorgiou et al [47] and Mukherjee et al [48], while the paper by Nadzharya et al [49] examines the influence of different spatial scales on the macroscopic behaviour of MS elastomers.…”
Section: Introductionmentioning
confidence: 99%
“…Yarali et al [32] presented a review on MERPs, focusing on their synthesis, characterization, and applications. Saber and Sedaghati [111] recently provided a study exclusively devoted to modeling, specifically concentrating on the dynamic and thermal behavior of MREs. Recently, Lu et al [112] presented an exclusive review of mechanics (outlining different constitutive models and principles) and design optimizations in hMSMs with a special focus on magnetic metamaterials.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, Sun et al [12] have demonstrated that an augmentation in magnetic flux leads to smoother frequency response peaks, attributed to an amplified damping effect within the structure. Several other authors have investigated the viscoelastic modeling of MREs and their application [13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%